Faktor-Faktor yang Dapat Memengaruhi Keterlambatan Diagnosis Kanker Payudara Stadium III di RSUD AL-Ihsan Bandung - Fauzia Azzahra; Nurhalim Shahib; Yusuf Heriady (UNISBA Press, 2023)
Abstract. Breast cancer is a malignant proliferation originating from breast epithelial cells lining the ducts of the breast lobules. Southeast Asia has a higher prevalence of breast cancer than other continents, with an incidence of 13.5% and a mortality rate of 9.7%. Meanwhile, the incidence of breast cancer in Indonesia reaches 16.7%, with a mortality rate of 21.4%. Stage III cancer has a higher risk of recurrence than other types of cancer – a delay in diagnosis when the patient enters stage III results in a lower prognosis and survival rate. Several factors cause delays in diagnosing cancer patients, including the patient's education level, economic status, and their preference for alternative treatments. This study aims to see if there is a link between education level, economic status, and a history of alternative medicine and a late diagnosis of stage III breast cancer at Al-Ihsan General Hospital in Bandung.This study used an observational analytic study design with a cross-sectional approach. The sample in this study was 47 patients with stage III cancer at Al-Ihsan Hospital, Bandung City. The results of the analysis using Chi-square showed that there was no meaningful relationship between educational level (p-value = 0.271), there was a significant relationship between economic status (p-value = 0.049), and there was an important relationship between alternative therapy (p-value = 0.012). The results of this study indicate that there is an important relationship between economic status and alternative therapies and delays in the diagnosis of stage III breast cancer at Al-Ihsan Hospital in Bandung, but there is no significant relationship with education level. Abstrak. Kanker payudara merupakan proliferasi ganas yang berasal dari sel epitel payudara yang melapisi saluran lobulus payudara. Asia Tenggara memiliki prevalensi kanker payudara lebih tinggi dari benua lain yaitu insidensinya mencapai 13,5% dengan mortalitas 9,7%. Sedangkan insidensi kanker payudara di Indonesia mencapai 16,7% dengan tingkat mortalitas sebanyak 21,4%. Kanker stadium III memiliki risiko kekambuhan yang tinggi dari jenis kanker lainnya. Keterlambatan dalam diagnosis pada saat pasien memasuki stadium III menyebabkan prognosis dan tingkat ketahanan hidupnya lebih rendah. Beberapa faktor yang menyebabkan keterlambatan dalam mendiagnosis pasien kanker tersebut antara lain rendahnya tingkat pendidikan pasien, status ekonomi, dan pasien lebih memilih pengobatan alternatif. Penelitian ini bertujuan untuk mengetahui hubungan tingkat pendidikan, status ekonomi, riwayat pengobatan alternatif dengan keterlambatan diagnosis kanker payudara stadium III di RSUD Al – Ihsan Bandung. Penelitian ini menggunakan rancangan studi analitik observatif dengan pendekatan cross sectional. Sampel pada penelitian ini yaitu 47 pasien penderita kanker stadium III di RSUD Al-Ihsan Kota Bandung. Hasil analisis menggunakan Chi-square menunjukan tidak terdapat hubungan yang bermakna antara tingkat pendidikan (p-value=0,173), terdapat hubungan yang bermakna antara status ekonomi (p-value=0,049) dan terapi alternatif (p-value=0,012). Hasil penelitian ini menunjukan terdapat hubungan yang bermakna antara status ekonomi dan terapi alternatif dengan keterlambatan diagnosis kanker payudara stadium III di RSUD Al-Ihsan Kota Bandung akan tetapi tidak terdapat hubungan yang bermakna dengan tingkat pendidikan.